Pengawasan Keimigrasian Terhadap Pengungsi Luar Negeri di Indonesia dalam Implementasi Peraturan Presiden No 125 tahun 2016 - Winda Rahmadhani Purwanti; M Syaprin Zahidi; Mochd Agoes Aufiya (Jurnal Intervensi Sosial dan Pembangunan, 2022)
This study aims to determine immigration control in dealing with refugees from abroad in Indonesia in the implementation of presidential regulation no 125 of 2016 where migration monitoring is necessary due to the increasing number of people who come to Indonesia as asylum seekers and refugees. The research method used is descriptive qualitative method where this method is one type of research method that seeks to describe and interpret objects as they are. The results of this study find that better monitoring is needed because foreign refugees are in a country where their rights must be protected. They represent the dilemma of the immigrant threat, especially when they bring different cultures and traditions into the local community. Supervision of Indonesian refugees held in immigration detention centers is well implemented on the spot. Monitoring programs in shelters, out of shelters, sent to destination countries, voluntary returns and deportations do not address issues related to the presence and activities of refugees while in Indonesia.Keywords: Presidential Regulation, Refugees,Supervision